Do regional trade pacts benefit the poor? : an illustration from the Dominican Republic-Central American free trade agreement in Nicaragua - Bussolo, Maurizio 1964- (Policy research working paper, 2006)
"The main objective of this paper is to provide an ex-ante assessment of the poverty and income distribution impacts of the Central American Free Trade Area agreement on Nicaragua. The authors use a general equilibrium macro model to simulate trade reform scenarios and estimate their price effects, while a micro-module maps these price changes into real income changes at the individual household level. A useful insight from this analysis is that even if the final total impact on poverty is not too large, its dispersion across households-due to their heterogeneity of factor endowments, inputs use, commodity production, and consumption preferences-is significant and should be taken into account when designing compensatory policies. Additionally, growth and redistribution decomposition show that, at least in the short to medium run, redistribution can be as important as growth. The main policy message that emerges from the paper is that Nicaragua should consider enlarging its own liberalization to countries other than the United States to boost trade-induced poverty reductions. "--World Bank web site